Development of Learning Media Based Augmented Reality Electromagnetic Induction Subject Matter - Novie Amalia Izza Iksani; Nadi Suprapto (Studies in Philosophy of Science and Education, 2022)
Learning about electromagnetic induction in physics calls for a deeper comprehension of abstract ideas and ways of thinking. This article is part of a development research project on augmented reality-based learning materials focused on electromagnetic induction. Its goal is to assess the reliability and efficacy of augmented reality-based learning materials with a particular emphasis on the cognitive learning outcomes of students. The 4-D development model "Define, Design, Develop, and Disseminate" is used in the study. (1) It is extremely practical to apply learning media based on augmented reality electromagnetic induction subject matter. (2) As a result of trials carried out based on the outcomes of a mean N gain of 0.76, the cognitive learning outcomes of students improved. The independent t-test findings revealed a significant relationship between the two variables, with a significant 2 tails of 0.000 (3). Student replies revealed that the learning medium are extremely practicable to use, with an average percentage value of 87%. Thus, it is advised to use augmented reality-based learning media for physics ideas that call for high levels of knowledge and abstract thought.